Negotiating Legal Pluralism: Syncretism of Islamic Law and Balinese Adat in Pegayaman Village - Irawan; Zayadi; Saihu, Made; Darwis Hude; Nasaruddin Umar (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Pegayaman, the sole Muslim village in Bali surrounded by Hindu communities, offers a unique context for exploring the interaction between Islamic law and local Hindu cultural traditions. The study examined how Islamic law is negotiated and practiced in the context of Hindu cultural dominance. Using an empirical legal research framework with a socio-legal approach, data were collected through field observations and in-depth interviews with Muslim traditional leaders, religious figures, residents, and migrants. The findings indicated that syncretic practices in Pegayaman do not undermine the Islamic creed (‘aqidah) but rather reflect a process of internalizing and negotiating Islamic values within the local cultural context. Rooted in the base meme philosophy emphasizing cultural heritage, tolerance, and social harmony, these practices manifested in religious celebrations and social rituals. From an Islamic legal perspective, such adaptations may be regarded as ‘urf sahih provided they do not conflict with Sharia principles. Thus, the study highlighted the significance of contextualizing Islamic law in pluralistic societies, demonstrating that cultural accommodation need not imply theological compromise.